How workers’ emotional dissonance explains the association between customers’ relations, burnout and health in an Italian supermarket chain - Vignoli, Michela; Mazzetti, Greta; Converso, Daniela; Guglielmi, Dina (La Medicina del Lavoro, 2021)
Introduction: Dealing with customers has increasingly became a risk factor that organisations should be aware of. Having to deal with difficult customers, pupils, patients it has been found to be the second most frequent reported risk factor in the recent 2019 ESENER survey (61%, up from 58%), just after repetitive hand or arm movements. Objectives: The aim of the present study is to explore the relationship between negative relations with customers and its association with employees’ burnout and general health. Methods: Data were collected using an anonymous, self-report questionnaire employed in an Italian company working in the large-scale retail sector. The sample was composed of 610 employees (70% women) working in 28 supermarkets. Results: Results showed that negative customer relations were associated to higher levels of emotional dissonance (b = .25; p = .000), which in turn was associated with higher levels of burnout (b = .72; p = .017) and consequently to higher levels of poor general health (b = .03; p = .000). Conclusion: This study contributed to the current understanding of how negative relationship with clients could trigger a health impairment process which could lead to higher levels of burnout and poorer general health in employees. Findings suggest that organizations whose employees’ work activities are characterized by a daily contact with customers should implement interventions such as training activities in order to enhance the employees’ skills in dealing with custumers, for example on how to manage emotions at work.